1999
DOI: 10.1111/j.1469-7793.1999.0451m.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate‐induced mitochondrial depolarisation and perturbation of calcium homeostasis in cultured rat hippocampal neurones

Abstract: The objective of this study was to clarify the relationships between loss of mitochondrial potential and the perturbation of neuronal Ca2+ homeostasis induced by a toxic glutamate challenge. Digital fluorescence imaging techniques were employed to monitor simultaneously changes in cytoplasmic Ca2+ concentration ([Ca2+]i) and mitochondrial potential (ΔΨm) in individual hippocampal neurones in culture coloaded with fura‐2 AM or fura‐2FF AM and rhodamine 123 (Rh 123). In most cells (96 %) at 6‐7 days in vitro (DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 39 publications
(51 reference statements)
8
155
1
Order By: Relevance
“…Cyclosporin A is problematic as a permeability transition diagnostic with intact cells due to its ability to inhibit calcineurin and hyperphosphorylate proteins (Hallak et al 2001). The more selective methyl-4-valine cyclosporin did not afford convincing protection in our hands (Castilho et al 1999) although others report partial protection against deregulation (Khaspekov et al 1999;Vergun et al 1999;Alano et al 2002).…”
Section: Discussioncontrasting
confidence: 44%
“…Cyclosporin A is problematic as a permeability transition diagnostic with intact cells due to its ability to inhibit calcineurin and hyperphosphorylate proteins (Hallak et al 2001). The more selective methyl-4-valine cyclosporin did not afford convincing protection in our hands (Castilho et al 1999) although others report partial protection against deregulation (Khaspekov et al 1999;Vergun et al 1999;Alano et al 2002).…”
Section: Discussioncontrasting
confidence: 44%
“…It is characterized by a dramatic increase in [Ca 2 þ ] i following the activation of Ca 2 þ -permeable receptors, particularly glutamate receptors, even after the stimulus has ended, thought to be due to loss of the mitochondrial ability to buffer intracellular Ca 2 þ . [28][29][30][31] More recently, it was demonstrated that, in cerebellar granule neurons, NCX also participates in this process of secondary Ca 2 þ overload, 14 due to its loss of the ability to pump Ca 2 þ out of the cell, following its proteolytic inactivation by calpains upon exposure to glutamate, providing a new hypothesis for the origin of delayed Ca 2 þ deregulation. Hoyt et al 32 have shown in cultured rat forebrain neurons that, although reversal of NCX contributes to Ca 2 þ transients and to the immediate rise in intracellular Ca 2 þ levels upon exposure to glutamate, it has no effect in the mean peak increase caused by a prolonged exposure to glutamate nor does it contribute to neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, using a similar experimental model and looking at the NMDA-evoked electrophysiological and [Ca 2C ] i responses, showed that with ageing (26 months old rodents) there was a significant increase in responsiveness when compared with the 'middle-aged' (nine months old) neurons (Cady et al 2001). Interestingly, during attempts to develop an 'ageing in the dish' experimental model, it was reported that several of the functional features of the aged neurons as recorded in acute brain slice preparations from the aged animals (either hippocampal or cerebellar) developed during longer term primary neuronal cultures (Blalock et al 1999;Vergun et al 1999;Xiong et al 2004).…”
Section: Functional Consequencesmentioning
confidence: 99%